Antiproliferative activity of the methanolic extract of piper aduncum leaves on gastric cancer cells - Miranda-García, Víctor (2020)
The Piper aduncum, also known as “Matico” in Peru, is a plant used as a healing, anti-diarrheal, anti-inflammatory, anti-cancer and other traditional uses plus1; These effects have been demonstrated as the antimicrobial2 and cytotoxic effect, the latter using bioguided fractionation, observing the effect on leaf extracts with dichloromethane on KB cells (nasopharyngeal carcinoma)3 and the essential oil on lung carcinoma, colon adenocarcinomas, adenocarcinoma of breast, amelanotic melanoma, cervical carcinoma, prostate carcinomas, chronic myeloid leukemia and normal mouse fibroblasts; in addition to oral toxicity in mice, finding null and toxic antitumor effect4. In the present study, the in vitro antiproliferative activity of the methanolic extract of Piper aduncum leaves on the AGS cell line (gastric adenocarcinoma) acquired from the ECACC (European Authenticated Cell Culture Collection) was evaluated, using a colorimetric technique with the resazurine indicator, evaluating the results within 24 and 48 hours of having exposed the extract to different factors: 1000, 500, 250, 125, 62.5, 31, 15, and 7 ppm with cancer cells, to analyze the results the percentage of the difference in reduction between treated cells and control cells and from this data the percentage of growth inhibition was obtained. The IC50 was obtained at 24 hours with 131,5 ppm and at 48 hours with the IC50 it was 103,3 ppm, It can be evidenced that at 48 hours the effect becomes more potent having 100 % inhibition from 250 ppm of methanolic extract.